PERANCANGAN APLIKASI ABSENSI SMP TERANG BAGI BANGSA - ARI YUNUS HENDRAWAN; Bagus Aprilio; Ruth Aprilia Wesley (Electro Luceat, 2020)
Online attendance application can be created by database and interface design baseball on Android mobile system. This application is an application that will make it easier for admins and teachers to manage data and make it easier for teachers to attend school absences. In addition, this application can control the attendance and punctuality of teachers. The data processed by the application is in the form of data on the names of the teaching staff at the school along with the employee identification numbers. This application only has a few buttons on the main menu, so users don't feel bored seeing the buttons. The use case diagram shows from the side of the admin who supervises and regulates the running of the application for the attendance of teaching staff and Android users or users, in this case, the SMP Terang Untuk Bangsa teacher. The Class Diagram model describes the system structure in terms of defining the classes that will be made to build the system. This class diagram provides details of the flow of an application to be made. Flowcharts or flow charts show the flow in a program or system procedure logically. The design of the interface (interface) shows the home menu, class attendance menu, attendance input, and attendance results